Wimmer - "McAllister, Margaret" (Oxford Universty Press: Oxford, 2001)
Wimmer came to Jacob straightaway. Wimmer looks like a dog, with huge eyes and clever, neat manners. Jacob cannot bear to leave him. But what is he? Jacob's sister Polly is suspicious. What has he got to do with smooth-talking Dr Harper?
Keywords: Pets Juvenile fiction